A melhoria da gestão pública com enfoque na certificação ISO 9001:2008: um estudo de caso na bolsa eletrônica de compras BEC/SP - Pereira, Veruska Evanir (2012)
The theme Total Quality Management is widespread among the private companies in Brazil and it is seen as a guiding to a management of excellence and a competitive differential. In Brazilian Public Administration, the theme is approached, however, still quietly implemented specially in the Direct Administration. Aspects related to the implementation of a Quality Management System (QMS) which demand efforts of the whole organization, support of the top management level and meeting the requirements of the customers, although they are not consolidated in many organs of the Public Administration. The objective of this dissertation is to diagnose and to analyze the aspects of the implementation of the QMS in organs of the Public Administration of the State of São Paulo, its implementation phases, and to demonstrate possible gains in efficiency and effectiveness of management processes, considering its benefits, peculiarities, results, challenges, and the expectation of its customers. To this end, research was done in terms of implementation of QMSs in government agencies of the Direct Administration of the State of São Paulo, driving a case study at the Bolsa Eletrônica de Compras do Estado de São Paulo BEC/SP which implemented a Quality Management System - QMS in 2009 culminating in the ISO 9001:2008 certification in the year 2010. The used methodology was the case study and the ex-post-facto analysis. The main results obtained can highlight the characterization and analysis of data that enable typify the aspects of the implementation of a quality management system from the perspective of the NBR ISO 9001:2008 in relation to Public Administration of São Paulo agencies.